Fertility preservation for female patients with childhood, adolescent, and young adult cancer: recommendations from the PanCareLIFE Consortium and the International Late Effects of Childhood Cancer Guideline Harmonization Group. Issue 2 (February 2021) - Mulder, Renée L; Font-Gonzalez, Anna; Hudson, Melissa M; van Santen, Hanneke M; Loeffen, Erik A H; Burns, Karen C; Quinn, Gwendolyn P; van Dulmen-den Broeder, Eline; Byrne, Julianne; Haupt, Riccardo; Wallace, W Hamish; van den Heuvel-Eibrink, Marry M; et al.
Summary: Female patients with childhood, adolescent, and young adult cancer are at increased risk for fertility impairment when treatment adversely affects the function of reproductive organs. Patients and their families desire biological children but substantial variations in clinical practice guidelines reduce consistent and timely implementation of effective interventions for fertility preservation across institutions. As part of the PanCareLIFE Consortium, and in collaboration with the International Late Effects of Childhood Cancer Guideline Harmonization Group, we reviewed the current literature and developed a clinical practice guideline for fertility preservation in female patients who were diagnosed with childhood, adolescent, and young adult cancer at age 25 years or younger, including guidance on risk assessment and available methods for fertility preservation. The Grading of Recommendations Assessment, Development and Evaluation methodology was used to grade the available evidence and to form the recommendations. This clinical practice guideline leverages existing evidence and international expertise to develop transparent recommendations that are easy to use to facilitate the care of female patients with childhood, adolescent, and young adult cancer who are at high risk for fertility impairment. A complete review of the existing evidence, including a quality assessment, transparent reporting of the guideline panel's decisions, and achievement of global interdisciplinary consensus, is an important result of this intensive collaboration.